Pengenalan Nilai Seni Nusantara Pada Anak Usia Dini Melalui Tari Kreasi Wonderland - Putri, Ni Putu Witari; Sukendri, Nengah; Wiguna, Ida Bagus Alit Arta; Andari, Ida Ayu Made Yuni (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2024)
Art education in early childhood has an important role in shaping the foundation of their development. One aspect that should not be missed is the introduction of Nusantara art values, which is an inseparable part of Indonesia's cultural heritage. The purpose of this study is to add insight and children's ability to dance. This research discusses the introduction of Nusantara art values in early childhood through Wonderland Creation Dance, a concept that combines traditional dance elements with children's imagination. This study highlights the potential of Kreasi Wonderland Dance in introducing Nusantara art values, its impact on early childhood character development, and effective implementation strategies in the context of early childhood education. Through the introduction of Nusantara art through Kreasi Wonderland Dance, it is hoped that children can gain a fun art experience while building their appreciation for the nation's cultural heritage from an early age, forming positive character and personality, and maintaining the sustainability of Nusantara art and culture in the future.